EFFECT OF HUMIC ACID AND NUTRIENT SOLUTION PROSOL IN GROWTH , YIELD GARLIC (Allium sativum L.) AND CONTENT FROM FATTY ACID. - Zahwan, Thamir Abdullah; Aiith, Nadhim Ailiwi; Salih, Ziyad Khalaf (Diyala Agricultural Sciences Journal, 2013)
A field experiment was conducted during growing season (2008 – 2009) at Univ. of Tikrit -College of Agriculture. Horticulture and Landscape Experimental Station. to study the response of Allium sativum L. for humic acid treatments and spraying by nutrient solution Prosol at four concentration (0 ,0.5 , 1 , 2 ) g/L . The experiment was in split plot design in RCBD with three replications , The humic treatment considered as the main plot. The results showed that humic treatment gave significant increases in most characteristics studied, and gave production of 3.38 ton / donum . Spray treatment with 2 gm/ L concentration gave production of 3.34 ton/ donum . Treatment interaction between humic treatment and spraying with Prosol 2 g/L concentration gave the highest content from Fatty acid ( 20.75 , 78.63 , 322.61 , 662.70 , 23.63 , 677.59) microgram/ gm for (Myristic acid , Stearic acid , Palmatic acid , Linolenic acid , Oleic acid and Linoleic acid) respectively .